X-ray powder diffraction data for Palbociclib, C24H29N7O2. Issue 3 (September 2016) - Zheng, Shoujun; Peng, Jiankun; Xu, Kailin; Tang, Pei Xiao; Ma, Xiaoli; Huang, Yanmei; Chen, Lijuan; Li, Hui
Abstract : X-ray powder diffraction (XRPD) data for Palbociclib, C24 H29 N7 O2, are reported [ a = 18.182(2) Å, b = 11.508(1) Å, c = 5.041(1) Å, α = 81.282(7)°, β = 97.423(7)°, γ = 102.415(2)°, unit-cell volume V = 1013.1(4) Å 3, Z = 2, and space group P -1. All XRPD measured lines were indexed and no detectable impurities were observed.